Rehabilitation of Posterior Maxilla with Zygomatic and Dental Implant after Tumor Resection: A Case Report - YILDIZ, COŞKUN; UĞURLU, FAYSAL (My University, 2013)
Zygomatic implants have been used for dental rehabilitation in patients with insufficient bone in the posterior upper jaw, due to, for example, tumor resection, trauma, or atrophy. Zygomatic implants are an alternative to complex free or vascularized bone grafting and distraction osteogenesis. A 42-year-old male patient with a severe defect in the right posterior maxilla, starting from the first canine region, which had occurred after tumor resection 3 years earlier, was referred to our department. One zygomatic implant (Brenemark System, Nobel Biocare, Goteborg, Sweden) to the zygoma and one dental implant to the canine region were placed. After a 5-month osseointegration period, a fixed denture was fabricated and adapted to the implants. Although the surgical and prosthetic procedures for zygoma implants are not easy, the final outcomes can be successful with appropriate planning.